2008
DOI: 10.1186/bcr2202
|View full text |Cite
|
Sign up to set email alerts
|

Y-box binding protein-1 serine 102 is a downstream target of p90 ribosomal S6 kinase in basal-like breast cancer cells

Abstract: IntroductionBasal-like breast cancers (BLBC) frequently overexpress the epidermal growth factor receptor (EGFR) and subsequently have high levels of signaling through the MAP kinase pathway, which is thought to contribute to their aggressive behavior. While we have previously reported the expression of Y-box binding protein-1 (YB-1) in 73% of BLBC, it is unclear whether it can be regulated by a component of the MAP kinase signaling pathway. Phosphorylation of YB-1 at the serine 102 residue is required for tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
170
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(176 citation statements)
references
References 52 publications
(79 reference statements)
5
170
0
Order By: Relevance
“…Indeed, we have recently demonstrated that RSK, similar to AKT, can phosphorylate YB-1 on its S102 residue in BLBC (Stratford et al, 2008). Our findings suggest the presence of a positive feedback loop by which P-YB-1 (S102) induces p110a, increasing PI3K activity, thereby leading to further increases in P-RSK.…”
Section: Mda-mb-231mentioning
confidence: 61%
See 2 more Smart Citations
“…Indeed, we have recently demonstrated that RSK, similar to AKT, can phosphorylate YB-1 on its S102 residue in BLBC (Stratford et al, 2008). Our findings suggest the presence of a positive feedback loop by which P-YB-1 (S102) induces p110a, increasing PI3K activity, thereby leading to further increases in P-RSK.…”
Section: Mda-mb-231mentioning
confidence: 61%
“…Once p110a is induced its kinase activity is upregulated leading to the activation of signaling through either AKT or RSK depending on whether PIK3CA is mutated. Activated AKT (Sutherland et al, 2005) or RSK (Stratford et al, 2008) phosphorylates YB-1 on its S102 site thereby allowing it to shuttle into the nucleus where it binds to the PIK3CA promoter to induce more p110a. This feedforward loop also causes an activation of signaling through RSK that enhances cellular invasion through phosphorylation of IkBa (Ghoda et al, 1997), allowing NFkB to enter into the nucleus where it can induce uPA production (Sliva et al, 2002).…”
Section: Mda-mb-231mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there being no specific inhibitors of MNK1 available, we sought to identify other strategies to inhibit MNK1. RSK is the major kinase responsible for phosphorylating YB-1 at S102 (Stratford et al, 2008). Therefore, we addressed whether its inhibition would affect MNK1 levels.…”
Section: Inhibition Of Rsk Blocks Mnk1-mediated Trastuzumab Resistancementioning
confidence: 99%
“…YB-1 is an oncogenic transcription/translation factor whose expression is associated with relapse and poor overall survival in various malignancies, including breast cancer (Wu et al, 2006;Habibi et al, 2008). The p90 ribosomal S6 kinase (RSK) (Stratford et al, 2008), and to a lesser extent AKT (Sutherland et al, 2005), can phosphorylate YB-1 on S102, promoting its nuclear translocation. Within the nucleus, YB-1 binds to inverted CCAAT boxes of genes (Didier et al, 1988) including MDR1 (Bargou et al, 1997), EGFR (Wu et al, 2006), PIK3CA , MET ) and CD44 to increase their transcription and thereby promote tumor progression.…”
Section: Introductionmentioning
confidence: 99%